State-Level Renewable Energy Policy Implementation: How and Why Do Stakeholders Participate? - Rountree, Valerie; Baldwin, Elizabeth (Frontiers in Communication, 2018)
For most of the 20th century, large-scale, utility-owned power plants dominated electricity generation in the United States. Today, however, a growing share of electricity comes from renewable energy sources such as solar and wind energy, which are often small-scale and distributed. In the absence of significant national policies, the Renewable Portfolio Standard has emerged as the key state-level policy governing the deployment and use of renewable energy sources. While renewable energy offers new possibilities for clean energy generation, it also poses new regulatory and governance challenges as a wide range of stakeholders, such as the utilities, regulatory agencies, environmental and consumer advocacy groups, electricity generators, and private citizens, increasingly seek to influence how Renewable Portfolio Standards are implemented. In this study, we ask: how and why do stakeholders participate in decision-making about how these policies are implemented? Given the unique context of renewable energy policy, the long-term and iterative nature of renewable energy policy implementation, and the wide range of actors involved, we look at the suite of participatory opportunities available to stakeholders. We interview stakeholders in two states—Colorado and Nevada—to identify the mechanisms through which stakeholders participate and the incentives (or disincentives) that influence their willingness to do so. We find that, while decision makers in both states use a variety of mechanisms to engage stakeholders in decision-making, meaningful participation may be limited to stakeholder groups that are knowledgeable about the issues, have the resources to engage in long-term and sustained participation, and have long-standing relationships with decision makers and other stakeholders. Although many stakeholders participate in multiple types of processes to achieve a broader range of benefits, they often perceive their participation as superficial; and yet, their continued participation suggests they may play a long game, building coalitions, relationships, and knowledge to position themselves to influence decisions later on. Finally, we find that the regulatory environment influences which participatory processes are available, the incentives for participation, and ultimately the outcomes of stakeholder participation.